ANALISIS TINGKAT KEBUGARAN JASMANI SISWA KELAS XI SEKOLAH MENENGAH ATAS NEGERI 8 KOTA PADANG - Mely Hasanah Lubis; Sepriadi; Aldo Naza Putra; Indri Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem addressed in this study is that the physical fitness level of Grade XI students at SMA Negeri 8 Padang has not yet been identified. This study aimed to determine the physical fitness level of Grade XI students at SMA Negeri 8 Padang. The research was conducted at SMA Negeri 8 Padang in May 2026. This study employed a quantitative research design using descriptive analysis. The population consisted of all Grade XI students of SMA Negeri 8 Padang, totaling 345 students, comprising 164 male students and 181 female students. The sample was selected using the proportional random sampling technique. A total of 10% of the male students and 10% of the female students were selected, resulting in a sample of 34 students, consisting of 16 male students and 18 female students. Data were collected using the Indonesian Student Fitness Test (Tes Kebugaran Siswa Indonesia/TKSI) Phase F for senior high school students, which includes the Hand-Eye Coordination Test, Hand Touch Reaction Test, T-Test, Vertical Jump Test, Dipping Test, and Multi-Stage Fitness Test. The results showed that the average physical fitness score of Grade XI students at SMA Negeri 8 Padang was 15.88. This result indicates that the physical fitness level of Grade XI students at SMA Negeri 8 Padang falls into the low category.